Theoretical study of a double-slope solar still with solar air heater condenser - Ahmed Ghazy (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
Despite their limited water production and efficiency, double-slope solar stills are an appropriate solution for water scarcity in hot arid regions. Numerous studies have focused on enhancing the effectiveness of double-slope solar stills. In this context, this study introduces a double-slope solar with a solar air heater condenser (DSSS-SAHC). The back cover of a conventional double-slope solar still was replaced by a glass air heater in order to recover the still’s thermal losses in heating air. The transient performance of the DSSS-SAHC was investigated numerically under real weather conditions and compared to the performance of a conventional double-slope solar still (CDSSS) with the same aspects. The impact of various weather and operation factors on the DSSS-SAHC performance was investigated at air flows of 0.01 and 0.1 kg/s to account for both natural and forced air circulation, respectively. The results revealed an increase of about 15% and 6% in the thermal efficiency of the DSSS-SAHC over that of the CDSSS, respectively, at air flows of 0.1 and 0.01 kg/s despite the DSSS-SAHC distillate was insignificantly greater than that of the CDSSS at both air flows. In addition, the water distillate of the DSSS-SAHC increased as the solar irradiance increased, the ambient wind and ambient temperature had contrary effects on the efficiency, and the initial saline water level had a negligible impact on the overall performance